PowerPoint 2007 just the steps for dummies - Obermeier, Barbara (For dummies, 2007)
When you're trying to harness the power of PowerPoint, you don't want to wade through lots of background and definitions; you want to make things happen! Power Point Just the Steps for Dummies puts your hands and eyes to work immediately so you can finish any PowerPoint project in a flash.